Mathematical problem solving ability of 8th grade students in terms of adversity quotient using discovery learning - Istiqomah, Sayidah Nur; Suyitno, Hardi; Safa'atullah, Muh. Fajar (Unnes Journal of Mathematics Education, 2021)
The purpose of this research was to (1) find out the completeness of mathematical problem-solving abilities of 8th-grade students in Discovery Learning; (2) description of mathematical problem-solving abilities aspects of 8th-grade students who have a climbers types; (3) description of mathematical problem-solving abilities aspects of grade 8th students who have a campers types; (4) description of mathematical problem-solving abilities aspects of 8th-grade students who have a quitters types. This research is mixed methods using a sequential explanatory model. The design is a one-shot case study. The sample class is 8D. Research subjects consisted of 2 students of climbers types and 4 students of climbers types. The results showed that (1) mathematical problem-solving abilities of 8th-grade students in Discovery Learning achieved classical and individual completeness; (2) climbers students can solve all of the problem-solving indicators; (3) ) campers students can solve three of problem-solving indicators; (4) quitters students were not found in this research so couldn’t be described.